Trajectories of socially anxious behavior from age 5 to 13: Temperamental and sociocognitive pathways. Issue 5 (11th April 2022) - Poole, Kristie L.; Degnan, Kathryn A.; Harrewijn, Anita; Almas, Alisa; Fox, Nathan A.; Henderson, Heather A.
Abstract: The authors examined temperamental and sociocognitive predictors of socially anxious behavior from preschool to early adolescence. Children ( N = 227; 59% male; 69% White) completed a speech task at ages 5, 7, 10, and 13 and socially anxious behaviors were coded. Behavioral inhibition (BI) was assessed at ages 2/3 and Theory of Mind (ToM) was assessed at age 4. Data collection occurred between 2003 and 2016. Three trajectories of socially anxious behavior were identified: high stable, average increasing, and low stable. Higher BI was related to the high stable trajectory, whereas lower ToM was related to the increasing trajectory of socially anxious behavior. There are heterogenous pathways of socially anxious behavior, which may be uniquely influenced by early temperamental and sociocognitive factors.